Research and education directions in Medical Informatics at the Aristotle University of Thessaloniki - Maglaveras, Nicos; Pappas, C. (Yearbook of Medical Informatics, 2003)
The field of Medical Informatics is one of the most active fields both in research and education at the Aristotle University of Thessaloniki. The nucleus of this scientific field at the Aristotle University resides in the Medical School and in particular in the Laboratory of Medical Informatics. Education programs exist in undergraduate, graduate and post-graduate levels, and are targeted towards medical students and doctors and information technology related students and professionals. Research projects cover a wide area of medical informatics including medical information processing and management, electronic health records design and implementation, medical decision support, biological systems simulation, telemedicine applications, integration and communication issues related to regional health information systems, and quality assessment of health services and systems. The description and brief presentation of the output of these educational and research directions shall be presented in this paper.